A Combination of Preoperative Computed Tomography-Defined Sarcopenia and Systemic Inflammation on Survival in Patients with Poorly Differentiated Neuroendocrine Neoplasms Following Radical Resection. (13th December 2022) - Jia, Jie; Zeng, Xiangyu; Li, Chengguo; Yang, Lei; Huang, Yongzhou; Tong, Xin; Jiang, Qi; Zhang, Peng; Tao, Kaixiong
Abstract: This retrospective study of 122 patients with gastrointestinal poorly differentiated neuroendocrine neoplasms (GI-PDNEN) who underwent radical resection between January 2010 and December 2020 aimed to investigate the usefulness of combined computed tomography (CT)-defined sarcopenia and systemic inflammation to evaluate long-term prognoses for patients who underwent radical surgical resection. Sarcopenia, based on a pre-defined L3 skeletal muscle index cutoff value, was assessed using preoperative abdominal CT images. Patients (neuroendocrine carcinoma, 86 patients; mixed adenoneuroendocrine carcinoma, 36 patients) were divided into low-, intermediate-, and high-risk groups using sarcopenia scores and neutrophil-to-lymphocyte ratios (SNLRs). Higher SNLRs were significantly associated with higher age ( P  = 0.004), larger tumor size ( P  = 0.042), lower body mass index ( P  = 0.042), and lower hemoglobin ( P  = 0.001) and albumin ( P  = 0.031) levels. Multivariate analysis indicated that a higher SNLR was an independent risk factor for poor overall survival (OS, P  = 0.01) and relapse-free survival (RFS, P  = 0.001) in patients with GI-PDNEN postoperatively. Sarcopenia and a higher NLR were significantly associated with poor RFS and OS following radical resection. The SNLR had a definite predictive prognostic value in preoperatively identifying patients with GI-PDNEN and a probable poor long-term prognosis, especially those with neuroendocrine carcinoma.